2015
DOI: 10.1097/qad.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

Associations of common variants in the BST2 region with HIV-1 acquisition in African American and European American people who inject drugs

Abstract: Objective The bone marrow stromal cell antigen 2 (BST2) gene encodes a host restriction factor that acts as an innate immune sensor of HIV-1 exposure and suppresses release of HIV-1 particles. We aimed to identify associations of variants in the BST2 gene region with HIV-1 acquisition and disease progression. Design/methods Using HIV+ cases and HIV- controls from the Urban Health Study (N=3,136 African Americans and European Americans who inject drugs), we tested 470 variants in BST2 and its flanking regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
(73 reference statements)
0
13
0
1
Order By: Relevance
“…The protective role of BST-2 was corroborated by recent findings in cohorts of HIV-1 seroprevalent drug users with BST2 variants that showed a higher BST2 transcription and slower progression to AIDS by rs3217318 and rs10415893 in a Spanish cohort[13], and also in prevention to horizontal transmission by rs113189798 in a North American cohort [14]. …”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The protective role of BST-2 was corroborated by recent findings in cohorts of HIV-1 seroprevalent drug users with BST2 variants that showed a higher BST2 transcription and slower progression to AIDS by rs3217318 and rs10415893 in a Spanish cohort[13], and also in prevention to horizontal transmission by rs113189798 in a North American cohort [14]. …”
Section: Discussionmentioning
confidence: 58%
“…An insertion/deletion polymorphism at the promoter region (rs3217318) and a single nucleotide polymorphism (SNP, rs10415893) of BST2 gene (located at 19p13.1) were associated with lower transcriptional levels of BST2 and faster disease progression in a Spanish cohort[13], while rs113189798 SNP was described as a risk factor to HIV-1 acquisition in North American seroprevalent drug users[14]. …”
Section: Introductionmentioning
confidence: 99%
“…For the UHS cohort, we acquired directly genotyped data and imputed data through dbGaP accession number phs000454.v1.p1. The UHS cohort was genotyped on the HumanOmni1-Quad_v1-0_B platform and then imputed in IMPUTE2 using 1000 Genomes phase 1 version 3 as the reference panel by the original authors in Hancock et al [10]. …”
Section: Methodsmentioning
confidence: 99%
“…The BST‐2 gene is located on chromosome 19, covering a region of 2.71 kb . Evidence suggests that BST2 acts as an innate immune sensor of HIV‐1, which produces an inflammatory response upon viral exposure, whereas a 19‐bp insertion allele in the BST2 rs3217318 polymorphism at position ‐411 was considered as a possible risk factor for HIV‐1/AIDS disease progression and an intergenic SNP rs113189798 was described as a risk factor for HIV‐1 acquisition in the North American seroprevalent drug users . Skelton et al .…”
Section: Introductionmentioning
confidence: 99%
“…29 Evidence suggests that BST2 acts as an innate immune sensor of HIV-1, which produces an inflammatory response upon viral exposure, [30][31][32][33] whereas a 19-bp insertion allele in the BST2 rs3217318 polymorphism at position -411 was considered as a possible risk factor for HIV-1/AIDS disease progression 34 and an intergenic SNP rs113189798 was described as a risk factor for HIV-1 acquisition in the North American seroprevalent drug users. 35 Skelton et al 36 suggested that promoter region polymorphisms in BST2 gene (rs73921425 and rs12609479) potentially altered transcription factor binding sites. Insertion/deletion (indels) polymorphisms in the promoter region (rs3217318 and rs10415893) of the BST2 gene were associated with lower transcriptional activity and faster disease progression in a Spanish cohort.…”
mentioning
confidence: 99%